2012
DOI: 10.4172/2155-6156.s2-002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: Early Development and Aging

Abstract: Adult metabolic and heart diseases have their origin early during intrauterine development and childhood. They can be traced to the inherited genome but patterns of cellular gene expression appropriate to the environment during development (epigenetics) also play an important role. This is particularly important during critical periods of time where structural and functional changes known as critical windows. There is a critical window of the pancreas when, if changes in diet occur, the risk of metabolic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 91 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…The term also refers to the deterioration of biological functions after an organism has attained its maximum reproductive potential [1,2]. Aging is accompanied by a chronic inflammatory state which may contribute to metabolic syndrome (MS) and diabetes and their cardiovascular consequences.…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…The term also refers to the deterioration of biological functions after an organism has attained its maximum reproductive potential [1,2]. Aging is accompanied by a chronic inflammatory state which may contribute to metabolic syndrome (MS) and diabetes and their cardiovascular consequences.…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…When insulin [64] was discovered, it was felt that diabetes was curable. Insulin is a master regulator of metabolic homeostasis [65] and it is secreted from pancreatic beta cells in response to nutrient stimulation. Insulin is used for treatment of type 1 diabetes mellitus, which is characterized by lack of the internally produced hormone [66].…”
Section: Role Of Insulinmentioning
confidence: 99%
“…A very consistent finding in all of these studies is that the prevalence of the MetS is highly age dependent. 6 Increases in waist circumference predominate among women, whereas increases in fasting plasma triglyceride levels , reductions in HDL cholesterol levels and hyperglycemias are more likely in men. 10 Indian studies among adults have reported prevalence varying from 13%-24.9% in northern India to 41% in southern India using different definitions.…”
Section: Introductionmentioning
confidence: 99%